Metformin Reduces Oxidative Stress Status and Improves Plasma Insulin Level in Streptozotocin-Induced Diabetic Rats - Usman, Umar Zayyanu; Abu Bakar , Ainul Bahiyah; Mohamed, Mahaneem (Journal of Pharmacy and Nutrition Sciences, 2016)
Background: Oxidative stress induced by hyperglycaemia plays a crucial role in the development of diabetic complications and metformin is commonly used in treating diabetes mellitus (DM). The aim of this study was to investigate whether metformin at the dose of 100 mg/kg/day could ameliorate oxidative stress and improve plasma insulin level in streptozotocin-induced diabetic rats. Methods: Twenty one rats (8-10 week old; weighing 190-220 g) were assigned into three groups (n=7 rats per group) i.e. non-DM, DM and DM+metformin (100 mg/kg/day metformin) groups. DM was induced using streptozotocin (60 mg/kg) intraperitoneally and treatments were given daily by oral gavage for four weeks. The levels of plasma biomarkers such as fasting blood glucose, oxidant-antioxidant markers and insulin levels were analysed. Results: Fasting blood glucose, malonyldehyde and protein carbonyls levels were significantly higher while insulin, total antioxidant capacity, catalase and glutathione peroxidase levels were significantly lower in DM group compared to non-DM group. The levels of fasting blood glucose, malonyldehyde and protein carbonyls were significantly lower while levels of total antioxidant capacity, catalase and insulin were significantly higher in DM+metformin group compared to DM group. Conclusion: This study may suggest that metformin at the dose of 100 mg/kg/day for 4 weeks reduces oxidative stress status and improves plasma insulin level in streptozotocin-induced diabetic rats possibly through its antihyperglycaemic action.